Perspectives for using technology of laser thermolithography - Kryuchyn, A.A.; Lapchuk, A.S.; Bryts’kyi, A.I.; Kostyukevych, S.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Analyzed in this work are the requirements to an optical system for laser
thermolithographic recording. It has been shown that possibilities of this type recording
with decreasing the registered element sizes can be realized only when using special
measures for stabilizing both exposing radiation power and duration of laser pulses.
Using the thermolithographic method for making super-dense patterns also requires
creation of a specific system for dynamic focusing with accuracy better than 100 nm. It
has been shown that the specific heat of thermochemical reaction and thermal resistance
of a substrate are critical parameters for this method.